Model improvement for super-Nernstian pH sensors: the effect of surface hydration - Madeira, Gustavo Daniel M.; N. P. Dias Mello, Hugo José [UNESP]; Faleiros, Murilo C.; Mulato, Marcelo (Springer Nature, 2021)
The maximum sensitivity of pH sensors is given by the Nernst equation, and its theoretical value is 59.2 mV pH−1. However, countless sensors developed and reported in the literature have their sensitivity higher than the Nernstian limit. These are called super-Nernstian sensors. To understand the causes of this behavior, the sensitivity of polyaniline thin films was studied by evaluation of an important parameter: the hydration of the film’s surface. Sensitivities were measured before and after varied heat treatments, and the sensor's parameters were associated with the amount of water lost in the process. Polyaniline thin films were fabricated by galvanostatic electrodeposition in aqueous solution, and their sensitivity was measured before and after heating of the samples. An endothermic process, typical of evaporation, was revealed by the analysis of mass loss during the heating process. A decrease in the sensitivity of the films was observed after heating process. For comparison, polyaniline thin films were also fabricated by spin coating, in the absence of water, and their sensitivity proved to be smaller than for the galvanostatically fabricated ones and it did not change significantly after the heating processes. The results indicated that the Nernst model can be adjusted using a parameter (1 / r) related to the hydration of the surface of the sample, which directly affects the sensitivity of the thin films. The lowest reachable 1 / r value for samples containing no water is approximately 0.9. The parameter also describes the upper limits for the sensitivity of super-Nernstian sensors.